(untitled) (World Bulletin of Public Health, 2024)
Ventricular preexcitation syndrome means that the ventricular myocardium is activated by atrial impulses conducted along the accessory pathway (APT) before the impulses reach the ventricles through the normal conduction system of the heart. Manifestations of PVA are rare - from 0.15 to 3.1% of the general population, including 9% of the total number of children with cardiac arrhythmias. This disease manifests itself in different forms - from constant clinical and electrophysiological manifestations in the manifest form to the absence of any subjective and objective symptoms in the latent form. The clinical significance of PVA is determined by the fact that almost 80.0% of patients sooner or later develop tachyarrhythmic attacks, both paroxysmal (i.e., transient) and chronic (permanently recurrent form) tachyarrhythmias, atrial fibrillation, atrial flutter, which when under certain conditions, they transform into atrial and ventricular fibrillation, which poses a threat to the patient’s life.